O efeito de sentido dos marcadores prosódicos gráficos na produção textual dos surdos - RODRIGUES, Ana Cristina Pontes (2019)
Cançado (2008) affirms that sense refers to the system of linguistic relations that a lexical item contracts with other lexical items. Following this perspective, we had as general objective to understand the effect of sense of the graphic prosodic markers of the Portuguese Language in the textual production of the deaf. Specifically, identify the recurrent punctuation marks in the textual production of the deaf; evidence the employment and textual functioning of punctuation in the written text of the Portuguese language as a second language for the deaf. In these terms, we assume that the meaning of the written text of the deaf, without the presence of graphic prosodic markers of the Portuguese language, can be captured by means of the concepts of existing words in the text. Thus, we adopt Pacheco (2006a) that reinforces the hypothesis of Cagliari (1982), when recognizing that "the signs of scoring function as prosodic markers"(p. 06). Participated in this study 3 (three) bilingual deaf in Libras/Portuguese, high school students regularly enrolled in schools in the municipality of Abaetetuba-Pará, which have aged between 18 to 24 years. They had the task of writing a letter to a very special person for them, and collect three letters produced by deaf participants. We see that the deaf used comma and end point in the genus letter, often inadequate in the text. These results indicate that the textual production of deaf can be understood by the semantic relation of lexical items, but not by the aspect of prosodic organization of language. Thus, when performing the reading for understanding of texts of the deaf must not only take into account the normative grammar, but mainly to understand the meaning of the content.